FAKTOR-FAKTOR YANG MEMPENGARUHI KARAKTER SISWA DALAM PEMBELAJARAN GEOGRAFI KELAS XI SMA NEGERI 1 TOMOHON - Lase, Mariana; Oroh, Hilda Vemy; Lobja, Xaverius Erick; Grystin Djein Sumilat; Ellen Eva Poli; Yemima Otoluwa (Fakultas Ilmu Sosial dan Hukum, 2025)
XI of SMA Negeri 1 Tomohon. This study uses a descriptive qualitative method. The subjects of this study were geography teachers and students at SMA Negeri 1 Tomohon. This study used reduction analysis techniques, data display, and conclusion drawing/verification. By collecting data through observation, interviews, and documentation. The results of this study indicate that the factors that influence student character in geography learning. It can be seen from the results of the interview that internal factors are the formation of character from the students themselves and encouragement from their surroundings. The second is external factors are factors consisting of family, cultural, and social school environments that help students grow and develop character. Where the attention and support of parents and the role of geography teachers are very influential in the formation of student character.